Maintaining stable LSPR performance of W18O49 by protecting its oxygen vacancy: A novel strategy for achieving durable sunlight driven photocatalysis - Feng, Chengyang; Tang, Lin; Deng, Yaocheng; Wang, Jiajia; Liu, Yani; Ouyang, Xilian; Chen, Zhaoming; Yang, Haoran; Yu, Jiangfang; Wang, Jingjing (Applied catalysis. B, Environmental, 2020)
[Display omitted] •A novel W18O49@g-C3N4 core-shell heterojunction was fabricated for the first time.•The g-C3N4 shell can effectively inhibit the deactivation of oxygen vacancies in internal W18O49.•The protective mechanism of oxygen vacancies has been studied and proposed.•A novel design strategy for stable nonstoichiometric semiconductor photocatalyst is developed. Nonstoichiometric plasmon semiconductors own excellent NIR absorption due to their unique LSPR effect, which shows great promise in the design and preparation of sunlight driven photocatalysts. The LSPR in such plasmon materials originates from the carrier collective oscillations of the lattice vacancies, so the stability of lattice vacancies determines the persistence of LSPR effect. Take W18O49 for example, the oxygen vacancies that provide LSPR effect will be oxidized and disappear after being used or exposed in the air for a long time, leading to the losing of NIR absorption ability. In order to inhibit the deactivation of oxygen vacancies, in this work, a layer of g-C3N4 shell is wrapped around the surface of W18O49 to isolate oxygen contact. The experiments proved that this strategy can greatly improve the stability of oxygen vacancies in W18O49, and make it maintain almost the same LSPR intensity after three-day aging experiment.